Maternal nutrition and its implications for fetal development - Maque-Ponce, Mary L. (2019)
A descriptive, bibliographic research study is based on the review and direct description of current topics related to Maternal Nutrition and its implications for fetal development. The design corresponds to the bibliographic research -removal of references exposed in written media or other media and the main objective of the study was to describe an adequate diet, with an important contribution of vita- mins and minerals, in the pregnant women and find the implications in the fetal development due to its shortcomings. As an instrument, a table for collecting information from secondary sources has been proposed, which helped to understand the implications of maternal nutrition in fetal development. It is concluded that the consumption of adequate levels of zinc in pregnancy helps the pregnant woman, to be resistant to infectious diseases; they can prevent an excessively long labor and help fetal growth. The lack of iodine during pregnancy can interfere with the development of the fetus and, in extreme cases, cause mental retardation, little growth and malformations in babies.